Stand Structure and Degradation Level of Mangrove Vegetation in Pongkar Village, Karimun Regency, Kepulauan Riau, Indonesia - Muhammad Alfandi Hasibuan; Yarsi Efendi; Fenny Agustina; Lani Puspita (Universitas Labuhanbatu, 2025)
Background: Mangrove ecosystems are globally significant for biodiversity, carbon storage, and coastal protection, yet they are increasingly threatened by anthropogenic activities. Indonesia, which hosts the world’s largest mangrove area, also experiences one of the highest degradation rates, making site-specific assessments essential. This study investigates the stand structure and degradation level of mangrove vegetation in Pongkar Village, Karimun Regency, Riau Islands Province, where ecological importance intersects with human pressures. Methodolgy: Field surveys were conducted using five 100 m transects with 10 × 10 m plots for vegetation analysis and a 1 ha plot to assess degradation levels following the Indonesian Ministry of Environment Decree No. 201/2004. Vegetation parameters, including density, frequency, dominance, and Importance Value Index (IVI), were measured. Results: Nine mangrove species were identified, comprising seven true mangroves and two associated species. Rhizophora apiculata dominated the community (density 0.078 ind/m²; IVI 121.15%). Diversity indices revealed medium diversity (H′ = 1.45–1.89), low to medium richness (Dmg = 1.28–1.78), high evenness (E = 0.81–0.86), and low dominance (D = 0.18–0.26). Stand density reached 1,181 trees/ha, classified as medium.These results suggest that ecological functions remain active, but moderate diversity and richness indicate vulnerability to disturbance and degradation risks. Contribution: The study provides empirical evidence to inform conservation planning, emphasizing the need for regular monitoring, rehabilitation of underrepresented species, and community-based management to sustain the Pongkar mangrove ecosystem